Temperature profiles in a micro-processor cooled by direct refrigerant evaporation = Analityczne rozwiązanie rozkładu temperatury wewnątrz mikroprocesora chłodzonego parującym czynnikiem chłodniczym - Lipnicki, Zygmunt; Lechów, Hanna; Pantoł, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An analytical solution to the equation for cooling of a unit, in the interior of which heat is generated, is presented. For that reason, a simplified non non-stationary model for determination of the temperature distribution within the unit, temperature of the contact between unit and a liquid layer, and the evaporating layer thickness in the function of time, is elaborated.
Keywords: wewnętrzne źródła ciepła; czynnik chłodniczy; ciecz chłodząca; grubość warstwy; odparowywanie; internal heat source; cooling; processor; vaprocompressor cycle; evaporation